Perception of Formative Competency Assessment and Virtual Course Satisfaction by Sex and Career Level among College Students - Morera-Castro, María (2023)
Purpose. This study aimed to establish the association between perceptions of formative competency assessment and the satisfaction level with the virtual courses based on sex and career level of university students in Costa Rica. Methodology. Six courses were selected for the study by convenience, with a sample of 127 students (61.35%) of 207 students enrolled in the first semester of 2021. Data collection utilized items from the Questionnaire on Methodology and Assessment in Physical Education Initial Training (QMAPEIT). Each student provided voluntary consent to participate; then the survey was administered in-class (synchronously) within a virtual environment. Results. The chi-squared analysis revealed a significant statistical difference by sex in the perception of the competence learning process when the formative assessment was used (χ2= 6.69, p= 0.035). Additionally, differences were observed in the perception of skill acquisition for their personal and professional life (χ2= 6.562, p=0.038), and in the level of general satisfaction with the course (χ2= 6.427, p= 0.040). Regarding the career level, a statistically significant difference was found between variables (p= 0.039). Conclusions. The findings of this research contribute to ongoing reflection, understanding, and improvement in the evaluation processes. This facilitates better quality of teaching and learning based on the differences in perception between men and women and their university career levels.